Los límites de la libertad religiosa en el derecho español (2007)
This article approaches the general matters relating to religious freedom in the Spanish legal order, by concentrating in the problems of its limits. In this sense, we will analyze the “public order” clause contained in article 16.1, and the concurrence of religious freedom with other fundamental rights. Subsequently, we will briefly refer to the suppositions of conscience objection (“objecion de conciencia”) recognized by the Spanish jurisprudence.